Fears for the future: the incommensurability of securitisation and in/securities among southern African youth. (4th May 2019) - Ansell, Nicola; Hajdu, Flora; van Blerk, Lorraine; Robson, Elsbeth
Abstract: Over the past two decades, southern Africa has experienced both exceptionally high AIDS prevalence and recurrent food shortages. International institutions have responded to these challenges by framing them as security concerns that demand urgent intervention. Young people are implicated in both crises and drawn into the securitisation discourse as agents (of risk and protection) and as (potential) victims. However, the concepts of security deployed by global institutions and translated into national policy do not reflect the ways in/security is experienced 'on the ground' as a subjective and embodied orientation to the future. This paper brings work on youth temporalities to bear on social and cultural geographies of in/security and securitisation. It reports on research that explored insecurities among young people in Lesotho and Malawi. It concludes that, by focusing on 'threats' in isolation, and seeking to protect 'society' as an abstract aggregate of people, global securitisation discourses fail either to engage with the complex contextualised ways in which marginalised people experience insecurity or to proffer the political responses that are needed if those felt insecurities are to be addressed. However, while securitisation is problematic, in/security is nonetheless an important element in young people's orientation to the future.